Fungal Diversity in Tomato Rhizosphere Soil under Conventional and Desert Farming Systems - Kazerooni, Elham A.; Maharachchikumbura, Sajeewa S. N.; Rethinasamy, Velazhahan; Al-Mahrouqi, Hamed; Al-Sadi, Abdullah M. (Frontiers in Microbiology, 2017)
This study examined fungal diversity and composition in conventional (CM) and desert farming (DE) systems in Oman. Fungal diversity in the rhizosphere of tomato was assessed using 454-pyrosequencing and culture-based techniques. Both techniques produced variable results in terms of fungal diversity, with 25% of the fungal classes shared between the two techniques. In addition, pyrosequencing recovered more taxa compared to direct plating. These findings could be attributed to the ability of pyrosequencing to recover taxa that cannot grow or are slow growing on culture media. Both techniques showed that fungal diversity in the conventional farm was comparable to that in the desert farm. However, the composition of fungal classes and taxa in the two farming systems were different. Pyrosequencing revealed that Microsporidetes and Dothideomycetes are the two most common fungal classes in CM and DE, respectively. However, the culture-based technique revealed that Eurotiomycetes was the most abundant class in both farming systems and some classes, such as Microsporidetes, were not detected by the culture-based technique. Although some plant pathogens (e.g. Pythium or Fusarium) were detected in the rhizosphere of tomato, the majority of fungal species in the rhizosphere of tomato were saprophytes. Our study shows that the cultivation system may have an impact on fungal diversity. The factors which affected fungal diversity in both farms are discussed.